2021
DOI: 10.1523/jneurosci.0345-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Phosphorylation as a Key Regulator of TRPM8 Channel Function

Abstract: In mammals, environmental cold sensing conducted by peripheral cold thermoreceptor neurons mostly depends on TRPM8, an ion channel that has evolved to become the main molecular cold transducer. This TRP channel is activated by cold, cooling compounds, such as menthol, voltage, and rises in osmolality. TRPM8 function is regulated by kinase activity that phosphorylates the channel under resting conditions. However, which specific residues, how this post-translational modification modulates TRPM8 activity, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 79 publications
4
16
0
Order By: Relevance
“…Only cells that responded to 50 µM Carbachol, a compound that activates endogenous muscarinic receptors in HEK-293 cells [29], were included in the analysis. [30][31][32], both for the EYFP and antibody signal, further confirming antibody specificity (Figure S1). No TRPM8 immunostaining was found in neighboring EYFP-(i.e.…”
Section: Resultssupporting
confidence: 66%
“…Only cells that responded to 50 µM Carbachol, a compound that activates endogenous muscarinic receptors in HEK-293 cells [29], were included in the analysis. [30][31][32], both for the EYFP and antibody signal, further confirming antibody specificity (Figure S1). No TRPM8 immunostaining was found in neighboring EYFP-(i.e.…”
Section: Resultssupporting
confidence: 66%
“…For TRPM4 channels, the Ca 2+ sensitivity has been shown to be regulated by protein kinase C–dependent phosphorylation at S 1152 and S 1145 within the C-terminus of the protein [ 32 ] and that casein kinase 1 (CK1)–mediated phosphorylation of S 839 is responsible for the basolateral localization of this channel in polarized epithelial cells [ 33 ]. Very recently, constitutive phosphorylation of four C-terminal serine residues has been identified as a key regulator of TRPM8 channels [ 34 ]. TRPM3 channels, however, have never been described as targets of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior could be attributed to a leftward shift of the voltage dependence of activation, thus, leading to a higher channel opening probability at physiological membrane potentials. In a recent study, the same authors identified S26 as a phosphorylation site, together with S29, S541, and S542, and showed that there is a TRPM8 downregulation by basal phosphorylation 64 . Point mutations to Ala in each of these Ser, showed that S29 is a key residue for TRPM8 modulation, as only the S29A mutation led to a strong potentiation of the response to cold and menthol.…”
Section: Trpm8 Mutantsmentioning
confidence: 98%
“…Based on previous studies on S26 and S27 it was argued that this mutation might influence the stability of the TRPM8 N ‐terminus. The identification of the key role of S29 led to the hypothesis that this R30Q might prevent S29 phosphorylation or the effect of this posttranscriptional modification 64 …”
Section: Trpm8 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation